Ceramic science and engineering : basics to recent advancements - Misra, Kamakhya Prakash; Misra, R. D. K. (Elsevier series on advanced ceramic materials., 2022)
Ceramic Science and Engineering: Basics to Recent Advancements covers the fundamentals, classification and applications surrounding ceramic engineering. In addition, the book contains an extensive review of the current published literature on established ceramic materials. Other sections present an extensive review of up-to-date research on new innovative ceramic materials and reviews recently published articles, case studies and the latest research outputs. The book will be an essential reference resource for materials scientists, physicists, chemists and engineers, postgraduate students, early career researchers, and industrial researchers working in R&D in the development of ceramic materials. Ceramic engineering deals with the science and technology of creating objects from inorganic and non-metallic materials. It combines the principles of chemistry, physics and engineering. Fiber-optic devices, microprocessors and solar panels are just a few examples of ceramic engineering being applied in everyday life. Advanced ceramics such as alumina, aluminum nitride, zirconia, ZnO, silicon carbide, silicon nitride and titania-based materials, each of which have their own specific characteristics and offer an economic and high-performance alternative to more conventional materials such as glass, metals and plastics are also discussed.